A note on linkage between gross value added and final use at the industry level. Issue 3 (2nd July 2020) - Cai, Junning; Leung, PingSun
ABSTRACT: Gross value added (GVA) is a common indicator of an industry/sector's economic performance. While an economy's total GVA is always equal to its total final use, an individual industry/sector's GVA is usually not equal to its final use. Yet an accounting identity between an industry/sector's GVA and the final use of multiple industries/sectors can be established by a gross value added-final use (GVA-FU) matrix. This paper derives the GVA-FU matrix in the Leontief demand-driven model and its equivalence in the Ghosh supply-driven model and interprets the matrix from different perspectives. The GVA-FU matrix can help policymakers and practitioners better understand an industry/sector's percentage of gross domestic product (GDP) – the underlying measure behind the United Nations Sustainable Development Goals (SDGs) Indicator 14.7.1 – from the demand-side perspective and facilitate its proper use for policy and planning. The GVA-FU matrix can become a standard component of the input–output apparatus for multiple applications.